2021
DOI: 10.1007/s00405-021-06723-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the European Laryngological Society classification of glottic vascular changes as seen by narrow band imaging in the optical biopsy setting

Abstract: Purpose In 2016, the European Laryngological Society (ELS) proposed a classification for vascular changes occurring in glottic lesions as visible by narrow band imaging (NBI), based on the dichotomic distinction between longitudinal vessels (not suspicious) and perpendicular ones (suspicious). The aim of our study was to validate this classification assessing the interobserver agreement and diagnostic test performance in detecting the final histopathology. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…The perpendicular changes present as intraepithelial papillary capillary loops (IPCLs) that are connected with laryngeal papillomatosis, precancerous, and cancerous lesions (27). Many authors confirmed the high accuracy of ELS classification in determining between benign and malignant lesions (28)(29)(30). In 2019, Ni et al improved the classification from 2011, adding another six types that cover vocal fold leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
“…The perpendicular changes present as intraepithelial papillary capillary loops (IPCLs) that are connected with laryngeal papillomatosis, precancerous, and cancerous lesions (27). Many authors confirmed the high accuracy of ELS classification in determining between benign and malignant lesions (28)(29)(30). In 2019, Ni et al improved the classification from 2011, adding another six types that cover vocal fold leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
“…In order to simplify this scale, the Committee on Endoscopic Laryngeal Imaging of the European Laryngological Society (ELS) proposed a two-tier classification of the vascular patterns [23]: longitudinal vascular changes are usually benign, whereas perpendicular vascular changes are stimulated by epithelial cancerogenesis, and related to premalignant or malignant lesions [41]. This classification has recently been validated in a study by Missale et al in a large multicenter cohort and has proved to be a highly reliable tool with good diagnostic performance in the optical biopsy setting [42].…”
Section: Nbi Classificationsmentioning
confidence: 99%
“…The basic principle of narrowband imaging technology is to narrow the white light wavelength of the xenon lamp into narrowband light waves of blue (wavelength 415 nm), green (wavelength 540 nm), and red (wavelength 600 nm) through special filters, mainly emphasizing blue light [ 1 ]. This narrowband light wave dominated by blue light has weak penetrating power and shallow irradiation depth and can only reach the surface of the tissue, thereby increasing the contrast and clarity of the mucosa, so it can clearly display the mucosal surface structure and gland duct opening shape [ 2 5 ]. In addition, due to the strong absorption of blue light by the optical characteristics of hemoglobin, NBI can also clearly display the submucosal microvascular morphology.…”
Section: Introductionmentioning
confidence: 99%